Ejercicios de Williams y McKenzie y sus beneficios en pacientes adultos mayores con dolor lumbar que acuden al Centro Gerontológico del Cantón Babahoyo periodo noviembre 2023 – abril 2024. - Coloma Adrián, Helen Xiomara (2024)
The present project is focused on verifying the general benefits of Williams and McKenzie exercises for low back pain in older adults attending the Babahoyo gerontological center. Low back pain or lumbar pain is pain in the lower back and is one of the main causes of disability when performing any task or activity of daily living throughout the world and can significantly affect quality of life. The main objective of the project is to identify the benefits of the exercises in question and to obtain good results, that is to say, to establish the objectives we want to achieve. A study will be carried out using questionnaires and interviews to collect habits, lifestyle and ergonomic conditions in the place where they reside. It is hoped that the results of the study will provide a deeper understanding of how the nature of the environment may influence the onset of low back pain. In addition, it seeks to establish possible associations with low back pain such as influencing factors like lifestyle, posture during task performance, and lack of physical activity. The relevance of this project lies in its potential to inform strategies on how to manage low back pain with these exercises specifically targeted to this group of older adults studied. It is hoped that the findings will contribute to improving environmental conditions, promoting the health and well-being of patients attending the gerontological center.